Preparation of biological antifreeze protein-modified emulsified asphalt coating and research on its anti-icing performance. (2nd August 2021) - Meng, Yongjun; Zhao, Qixiong; Lei, Jiechao; Mao, Mingliang; Qin, Yue; Xi, Chenchen; Lu, Zubiao; Yang, Xiaolong; Rong, Hongliu
Graphical abstract: Highlights: Bio-antifreeze protein is used to prepare pavement anti-freezing coating. The anti-freezing performance of bio-AFP-modified emulsified asphalt coating was tested. The road performance of bio-AFP-modified emulsified asphalt coating was tested. Abstract: Natural organisms use their own biological antifreeze proteins (AFP) to cope with cold environments. Based on this natural phenomenon, we herein use biological AFP and asphalt-based materials to prepare road anti-icing coating materials and subsequently study its storage stability and anti-icing performance. The storage stability test, fluorescence microscope analysis, scanning electron microscope analysis, and infrared spectrum analysis demonstrated that when the AFP powder content was not more than 5%, it was evenly dispersed in the emulsified asphalt, had good stability, did not undergo a chemical reaction, and retained the molecular activity of AFP. Combined with the anti-icing, pull-out, and falling ball impact tests, the addition of biological AFP powder demonstrates obvious anti-icing performance; furthermore, with an increase in the powder content, the anti-icing effect is improved. The road performance test showed that the coating had good durability and spalling resistance. When the spraying amount of the coating on the asphalt pavement is ≤ 0.4 kg/m 2, the BPN value and TD value meet the requirements of the specification. The application of a biological AFP-modified emulsified asphalt coating can significantly improve the anti-icing performance of roads and does not harm ecological environments.